Evolution of an oceanic anticyclone in the lee of Madeira Island: In situ and remote sensing survey. Issue 2 (20th February 2014) - Caldeira, Rui M. A.; Stegner, Alexandre; Couvelard, Xavier; Araújo, Isabel B.; Testor, Pierre; Lorenzo, Alvaro
Abstract Island wakes are areas of a strong eddy activity influencing the availability and transport of organic matter in the ocean which, in turn impact biological productivity. Despite this, eddy formation in the lee of North Atlantic tropical islands is scarcely documented, except for the Canary Islands. Moreover, the occurrence of anticyclones leeward of Madeira has seldom been detected. During the summer of 2011, a multiplatform approach, combining satellite data with in situ measurements, was used to study an anticyclonic eddy generated in the lee of the Madeira Island. The main objective was to confirm recent numerical evidence suggesting that orographically perturbed winds can induce anticyclonic eddies leeward of Madeira, particularly during summer months. The high resolution sampling of the eddy's interior shows a strong downwelling of ≈100 m of the isopycnal layer below the mixed layer, typical of intrathermocline eddies. The 25 km radius of this anticyclonic structure exceeds the local deformation radius by a factor of 2. The vortex Rossby number remained moderate (Ro = 0.26) even if the relative core vorticity reached a finite value (ζ/f = −0.7). The occurrence of strong trade winds (10–15 m s−1) prior to the detection of the first surface eddy signatures (July 2011) concurrent with opposite flowing geostrophic currents, shows that the orographic wind forcing is the main mechanism for generating this mesoscale long‐lived eddy. After leaving the shelter of the island, the eddy traveled northwesterly following a perpendicular net Ekman transport pathway at a speed of 5 km/d, for at least 2 months. An interaction with a cyclonic partner generated in the area helped precipitate the northward trajectory. This study presents the first clear evidence of a wind‐induced mesoscale anticyclone in the lee of Madeira.